PENJAMINAN MUTU PENDIDIKAN MELALUI TEKNOLOGI INFORMASI DI INSTITUT HINDU DHARMA NEGERI DENPASAR - Ngurah Triyana, I Gusti (Jurnal Penjaminan Mutu, 2017)
Institut Hindu Dharma Negeri (IHDN) Denpasar utilize information technology to support the vision and mission. Besides utilized to assist in the administration of education, information technology is also used for the development of quality IHDN. For example, the implementation of SPMI by the Lembaga Penjaminan Mutu (LPM) IHDN Denpasar by utilizing information technology in empowering educators, staff, service for learners. Information technology can make SPMI process becomes more transparent and accountable, so as to improve the quality of education in IHDN Denpasar.In 2016, the lecturers of IHDN Denpasar have been using applications Beban Kerja Dosen (BKD) so that the implementation of the Tri Dharma Perguruan Tinggi of each Lecturer can be calculated in a professional manner. Application Beban Kerja Dosen (BKD) which uses Microsoft Access greatly assist the lecturers of IHDN Denpasar in preparing the report of BKD, which became the basis allowances of lecturer certification. Scientific Journal Publication as research journals have been managed by using information technology in website’s form http://www.ejournal.ihdn.ac.id. Process research and community service in IHDN Denpasar, ranging from proposals to reporting already using online application that Management Information Systems Institute of Research and Community Service (LPPM). Implementation of the obligations of officials in Denpasar IHDN in education have used the system of financial information which relating to applications such as SPAN and SILABI, and for IHDN affairs personnel data in Denpasar using http://ropeg.kemenag.go.id information system. whereas for asset management or inventory in IHDN Denpasar is managed by using the application of State Property (BMN). Services to students, starting from recruitment of new students, the learning process through graduation in Denpasar IHDN also have been managed through a new Student Information System Admissions, Academic Information Systems, and Information Systems Graduation.